Selenium Alleviates Cadmium Toxicity by Regulating Carbon Metabolism, AsA-GSH Cycle, and Cadmium Transport in Glycyrrhiza uralensis Fisch. Seedlings - Xuerong Zheng; Jiafen Luo; Xin Li; Chaoyue Zhang; Guigui Wan; Caixia Xia; Jiahui Lu (Plants)
Cadmium (Cd) accumulation in plants hinders their growth and development while posing significant risks to human health through food chain transmission. Glycyrrhiza uralensis Fisch. (G. uralensis) is a medicinal plant valued for its roots and plays a crucial role in harmonizing various herbs in traditional Chinese medicine prescriptions. However, widespread Cd contamination in soil limits safe cultivation and application. Selenium (Se), a beneficial element in plants, can regulate plant growth by enhancing carbon metabolism and reducing heavy metal uptake. This study aimed to elucidate the protective mechanisms of Se application in licorice plants exposed to 20 μM Cd. Experiments with 1 and 5 μM of Se revealed that 1 μM of Se provided the best protective effects. This concentration reduced the Cd2+ content in the roots of G. uralensis, while significantly increasing plant biomass, root length, SPAD value, and contents of K+, Ca2+, and S2−. Additionally, the treatment reduced the malondialdehyde (MDA) content by 30.71% and 58.91% at 12 h and 30 d, respectively. The transcriptome analysis results suggest that Se mitigated Cd toxicity by enhancing carbon metabolism, regulating the AsA-GSH cycle, reducing Cd absorption, promoting Cd transport and compartmentalization, and modulating Cd resistance-associated transcription factors. These findings clarify the mechanisms by which Se alleviates Cd toxicity in G. uralensis and offer a promising strategy for the safe cultivation and quality control of medicinal herbs in Cd-contaminated soils.